Dampak Lingkungan Ekologis akibat Proyek Pembangunan Jalur Rel Light Rapid Transit (LRT) Jabotabek di Jakarta - Zulfahmi Bachtiar; Ramos Pasaribu (CV. Gio Architect, 2023)
Almost all developments of transportation facilities and infrastructure have positive and negative impacts on the ecological environment, social, and economic, such as the construction of rail lines and Light Rapid Transit (LRT) stations. The construction of rail lines and Light Rapid Transit (LRT) stations, both surface and elevated, has had various effects on the ecological environment, social and economic both during pre-construction, construction, and post-construction. The purpose of this paper is to identify the ecological environmental impacts due to green open space used for the construction of LRT rail lines and stations, especially the Jabodebek LRT line phase 1 in the city of Jakarta. This research was conducted by collecting data on the planning and construction of the 26 KM-long phases 1 rail line and LRT station. for the construction of rail lines and LRT station buildings. The results of the study show that with the rail pattern (elevated rail) it is possible to minimize the green open space used for the construction of rails and LRT stations. This study also recommends landscape proposals with vertical gardens on rail support pillars and station buildings as a substitute for some of the used green open space.